Biocompatibility of a porous alumina ceramic scaffold coated with hydroxyapatite and bioglass - Kido, Hueliton Wilian; Ribeiro, Daniel Araki; de Oliveira, Poliani; Parizotto, Nivaldo Antônio; Camilo, Claudia Cristiane; Fortulan, Carlos Alberto; Marcantonio, Elcio; Da Silva, Victor Hugo Pereira; Muniz Renno, Ana Claudia (Wiley, 2013)
This study aimed to evaluate the osteointegration and genotoxic potential of a bioactive scaffold, composed of alumina and coated with hydroxyapatite and bioglass, after their implantation in tibias of rats. For this purpose, Wistar rats underwent surgery to induce a tibial bone defect, which was filled with the bioactive scaffolds. Histology analysis (descriptive and morphometry) of the bone tissue and the single-cell gel assay (comet) in multiple organs (blood, liver, and kidney) were used to reach this aim after a period of 30, 60, 90, and 180 days of material implantation. The main findings showed that the incorporation of hydroxyapatite and bioglass in the alumina scaffolds produced a suitable environment for bone ingrowth in the tibial defects and did not demonstrate any genotoxicity in the organs evaluated in all experimental periods. These results clearly indicate that the bioactive scaffolds used in this study present osteogenic potential and still exhibit local and systemic biocompatibility. These findings are promising once they convey important information about the behavior of this novel biomaterial in biological system and highlight its possible clinical application. © 2013 Wiley Periodicals, Inc.
Keywords: Alumina; Biocompatibility; Bone repair; DNA damage